1992
DOI: 10.1007/bf02253596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diazepam on behavioural and antinociceptive responses to the elevated plus-maze in male mice depend upon treatment regimen and prior maze experience

Abstract: Recent studies have shown that brief exposure to an elevated plus-maze (EPM) produces non-opioid antinociception in male mice. The present experiments were designed to assess the effects of diazepam on this phenomenon. When acutely administered, low doses (0.5-1.0 mg/kg) of diazepam failed to produce an anxiolytic profile and exerted rather inconsistent effects on EPM-induced elevations in tail-flick latencies. In EPM-experienced mice, chronic treatment with higher doses of diazepam (2-4 mg/kg, 8 days) produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
6

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(86 citation statements)
references
References 44 publications
5
75
0
6
Order By: Relevance
“…5,6 ) and mechanisms (e.g., GABA, glutamate, serotonin, hypothalamic-pituitary-adrenal axis neuromodulators, etc. 1,3,[7][8][9][10][11][12] ) underlying anxiety behavior. Indeed, the elevated plus maze has been used as a model of state, unconditioned anxiety for over two decades, and there are now over 2,000 papers related to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 ) and mechanisms (e.g., GABA, glutamate, serotonin, hypothalamic-pituitary-adrenal axis neuromodulators, etc. 1,3,[7][8][9][10][11][12] ) underlying anxiety behavior. Indeed, the elevated plus maze has been used as a model of state, unconditioned anxiety for over two decades, and there are now over 2,000 papers related to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The open arm of the EPM is considered anxiogenic, or anxiety inducing; thus, rats exhibiting greater anxiety-related behavior will enter and spend less time in the open arms of the maze (Bertoglio and Carobrez, 2000;Pellow et al, 1985). The percentage of time spent on the open arm is increased and decreased with anxiolytic and anxiogenic substances, respectively (Bertoglio and Carobrez, 2000;Pellow et al, 1985;Rodgers et al, 1992). When used appropriately, the EPM is the most effective and popular animal model to observe and quantify anxiety within the rodent model (Rodgers and Dalvi, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the percentage of time spent on the open arms and open arm entries indicate an anxiolytic effect, such as caused by benzodiazepines. Surprisingly, rats and mice do not show habituation to anxiety (File 1990;File and Zangrossi 1993;File and Gonzalez 1996;Gonzalez and File 1997;Rodgers et al 1992;Rodgers and Shepherd 1993) or to the elevation in corticosterone (File et al 1994;Holmes et al 1998). Treit et al (1993) have found that on the first exposure to the plus-maze it is the open aspect of the arm, rather than its elevation, that is the main anxiogenic stimulus.…”
mentioning
confidence: 99%